The Role of Emotional Competence in Takotsubo Cardiomyopathy. Issue 4 (May 2018) - Compare, Angelo; Brugnera, Agostino; Spada, Marcantonio M.; Zarbo, Cristina; Tasca, Giorgio A.; Sassaroli, Sandra; Caselli, Gabriele; Ruggiero, Giovanni Maria; Wittstein, Ilan
ABSTRACT: Objective: The current study examined the role of emotional competences and depression in takotsubo cardiomyopathy (TTC). Methods: We compared 37 TTC patients who experienced emotion triggers (TTC-t: M (SD) age = 66.4 (12.8) years, 33 women) with 37 TTC patients who did not experience emotion triggers (TTC-nt: M (SD) age = 65.8 (11.1) years, 33 women) and 37 patients with acute myocardial infarction who experienced an emotion trigger (AMI-t: M (SD) age = 66.1 (10.1) years, 33 women). Three aspects of emotional competence (emotional intelligence, metacognitive beliefs, and emotional processing deficits) were assessed using the Trait Meta-Mood Scale (TMMS), the Meta-Cognitions Questionnaire 30, and the Emotional Processing Scale. Differences between-group means were evaluated using multivariate analysis of covariance, adjusting for depressive symptom (Hamilton Rating Scale for Depression). Results: Compared with the TTC-nt and AMI-t comparison groups, TTC-t patients had low scores on emotional intelligence (TMMS Attention: F (2, 184) = 23.10, p < .001; TMMS Repair: F (2, 184) = 11.98, p < .001) and high scores in metacognitive beliefs and emotional processing deficits (e.g., Meta-Cognitions Questionnaire 30 Negative Beliefs about Thoughts: F (2, 184) = 56.93, p < .001), independent of the levels of depressive symptom. TTC-nt patients also had significantly lower scores on the Hamilton Rating Scale for Depression scale compared with AMI-t ( p = .021) and TTC-t ( p = .004) patients. Conclusions: TTC-t patients showed a specific dysfunctional profile of emotional competence, even after adjusting for depressive symptom. These results provided a better understanding of the psychological factors that contribute to TTC. Abstract : Supplemental digital content is available in the text.